Development of the Text-Learning Strategies Inventory: Assessing and Profiling Learning From Texts in Fifth and Sixth Grade. (September 2014) - Merchie, Emmelien; Van Keer, Hilde; Vandevelde, Sabrina
Independently learning from informative texts becomes increasingly important from the age of 11. Little information is available, however, on (a) how and to what extent late elementary education students already apply specific text-learning strategies, and (b) whether different learner profiles can already be distinguished. In this study, a 37-item Text-Learning Strategies Inventory (TLSI) was developed and validated by means of exploratory (Sample 1; 896 students) and confirmatory factor analysis (Sample 2; 644 students). The TLSI contains nine subscales reflecting overt, covert, surface- and deep-level cognitive and metacognitive text-learning strategies. Based on these subscales, four learner profiles (i.e., integrated strategy users, information organizers, mental learners, and memorizers) were identified and validated by means of hierarchical and k-means cluster analysis and study traces. No differences in text free recall score between profiles were found. More girls were profiled as integrated strategy users, whereas more boys were identified as mental learners or memorizers.